A simple technique for the study of fish meiotic chromosomes - Bongso, Tuan Ariffeen; Mohammad Mohsin, Abu Khair; Siraj, Siti Shapor (Malaysian Society of Applied Biology, 1982)

(untitled)
A simple technique to study meiotic chromosomes from the testes of fish injected with colchicine is described. The minced testes was treated with a hypotonic solution of 0.075 M potassium chloride followed by fixation with Carnoy's solution. Air dried slides containing three to four drops of cell suspension were stained with 2 per cent aceto-orcein to display the various stages of meiosis. Clarity of chromosomes and adequate numbers of metaphase spreads per sample were obtained. Satisfactory results were also achieved for mitotic chromosomes when the same technique was used on gill preparations